Preparation of Hybrid Alginate-Chitosan Aerogel as Potential Carriers for Pulmonary Drug Delivery - Alnaief, Mohammad (Polymers (Basel), 2020)
This study aims to prepare hybrid chitosan-alginate aerogel microparticles without using additional ionic crosslinker as a possible pulmonary drug delivery system. The microparticles were prepared using the emulsion gelation method. The effect of the mixing order of the biopolymer within the emulsion and the surfactant used on final particle properties were investigated. Physicochemical characterizations were performed to evaluate particle size, density, morphology, surface area, surface charge, and the crystallinity of the preparation. The developed preparation was evaluated for its acute toxicity in adult male Sprague-Dawley rats. Measurements of zeta potential suggest that the surface charge depends mainly on the surfactant type while the order of biopolymer mixing has less impact on the surface charge. Chitosan amphiphilic properties changed the hydrophilic-lipophilic balance (HLB) of the emulsifying agents. The specific surface area of the prepared microparticles was in the range of (29.36–86.20) m(2)/g with a mesoporous pore size of (12.48–13.38) nm and pore volume of (0.09–0.29) cm(3)/g. The calculated aerodynamic diameter of the prepared particles was in the range of (0.17–2.29 µm). Toxicity studies showed that alginate-chitosan carrier developed herein caused mild lung inflammation with some renal and hepatic toxicities.